PENGEMBANGAN BUKU PANDUAN PRAKTIKUM BERBASIS INKUIRI TERBIMBING UNTUK GURU DALAM PEMBELAJARAN BIOLOGI KELAS X SMA - Desi Puspitasari; Yuslim Fauziah; Mariani Natalina L (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research was conducted to develop a guided inquiry-based practicum guidebook for teachers in teaching biology at the first year of senior high school students. It was conducted in September 2018 to January 2019. It Used a Research and Development (R&D) approach with Analysis Design Development Implement and Evaluations) model. This research was carried out to stage three, namely the depelopment stage. The data were obtained by both external, The external validation by one teacher of SMAN Plus and one teacher of SMAN Olahraga Pekanbaru. And internal validator which continued by limited trials. The trial I was tried on 10 student of the fourth semester of FKIP Biology UNRI and the trial II was tried on 20 Biology subject teacherswho joined the MGMP. Beside that, the phase II was carried out at the center of the SMA/MA Biology MGMP in Pekanbaru City. The book is validated based on four indicators, namely: book format and graphics, illustrations and pictures, language, and content eligibility. The overall results of the validation obtained an average of 3,50 with very valid categories. The results of the limited trial phase I have an average of 3,44 with very good categories and the results of the limited trial phase II have an average of 3,36 with very good categories. The book produced in this study has a very valid and very good categories so that the practicum guidebook can be implemented on a field scale.Key Words: Practicum guidebook, Quided Inquiry, Biology learning